Geriatric Dentistry - Surmounting the Challenges - P, Dr. Ranjith Kumar; Raghavan, Dr Rohit; Rahman, Dr. Nadeem Abdul; S, Dr. Sumitra; Vs, Dr. Monisha (International Journal of Innovative Research in Medical Science, 2016)
Geriatric dentistry is the branch of dentistry that emphasizes dental care for the elderly population and focuses upon patients with chronic physiological, physical and/or psychological changes or morbid conditions/ diseases. Gerodontics delivers dental care to older adults which involves diagnosis and treatment planning and prevention of problems associated with normal ageing and age-related diseases as an inter disciplinary manner with other medical professionals. Elderly patients are usually associated with oral manifestations due to various systemic conditions. It is important to alter the treatment mode with taking into account the psychological considerations of such patients. More stress must be given for prevention and early intervention to control the risk of oral diseases. It is important to educate dental professionals regarding the importance of geriatric services without any delay. This article makes an attempt to give the objectives, dietary guidelines and treatment considerations to meet the need of the geriatric patients.